Consumer economic problems - Warmke, Roman F.; Wyllie, Eugene D.; Wilson, William Harmon (Cincinnati : South-Western Pub. Co., 1977)
This book deals with the essentials of economic principles, business and consumer relations woven into a fabric of experiences .
First-3d ed. by H. G. Shields; 4th-7th ed. by W. H. Wilson.
Includes index.
oo 22/01/2019
Loans
Keywords: Consumer education; Consumers; Economics